Unravelling the Therapeutic Potential of Botanicals Against Chronic Obstructive Pulmonary Disease (COPD): Molecular Insights and Future Perspectives - Mitra, Sicon; Anand, Uttpal; Ghorai, Mimosa; Vellingiri, Balachandar; Jha, Niraj Kumar; Behl, Tapan; Kumar, Manoj; Radha,; Shekhawat, Mahipal S.; Proćków, Jarosław; Dey, Abhijit (Frontiers in Pharmacology, 2022)
Background: COPD (chronic obstructive pulmonary disease) is a serious health problem worldwide. Present treatments are insufficient and have severe side effects. There is a critical shortage of possible alternative treatments. Medicinal herbs are the most traditional and widely used therapy for treating a wide range of human illnesses around the world. In several countries, different plants are used to treat COPD. Purpose: In this review, we have discussed several known cellular and molecular components implicated in COPD and how plant-derived chemicals might modulate them. Methods: We have discussed how COVID-19 is associated with COPD mortality and severity along with the phytochemical roles of a few plants in the treatment of COPD. In addition, two tables have been included; the first summarizes different plants used for the treatment of COPD, and the second table consists of different kinds of phytochemicals extracted from plants, which are used to inhibit inflammation in the lungs. Conclusions: Various plants have been found to have medicinal properties against COPD. Many plant extracts and components may be used as novel disease-modifying drugs for lung inflammatory diseases.